Summer comfort in residential buildings and small offices, using sustainable cooling systems - De Pauw, Margot; Van der Veken, Jeroen (CLIMA 2022 conference, 2022)
Summer comfort gains attention due to climate change and increasing frequency of heat waves, also in small office buildings and even in residential dwellings. Active cooling systems, using an electric compressor and standard refrigerants, are widely used because of the high cooling power and comfort level they can guarantee. However, given the energy use and refrigerants inherent to those cooling systems, other more sustainable cooling systems should be considered in the first place. To accelerate the acceptance of sustainable cooling systems such as evaporative cooling or free geothermal cooling combined with high temperature emitters, and to ensure a large scale rollout of those systems, a more profound insight is needed into their performance and the provided level of comfort. In the framework of the CORNET project SCoolS the performance of different sustainable cooling systems is evaluated for a set of residential buildings and small offices by means of TRNSYS simulations. To do so, a new future climate file for Belgium has been constructed and comfort classes were defined. A parameter study varying insulation, thermal capacity, window percentage and orientation of the building was performed. Furthermore, the impact of adding passive cooling strategies like solar shading and intensive ventilation by window opening were analyzed. The SCoolS project resulted in a decision support tool for sustainable cooling systems. This article presents the preconditions and results with focus on the non-residential cases. Results show that in office buildings the necessary cooling loads are higher than in dwellings due to more concentrated heat gains during the day and often also more solar gains due to larger window surfaces. However, also in office buildings a combination of passive cooling strategies and sustainable cooling systems (coupled to floor or ceiling cooling) proves to be able to deliver excellent summer comfort.